Project-Based Teaching in Building Students' Intercurricular Competencies - Daliborka R. Popović; Мirjana R. Beara (University of Belgrade, Teacher Education Faculty, 2022)
Given that the focus of educational policy is aimed at creating real learning opportunities in the function of achieving educational results that prepare students for life, it is necessary to overcome the traditional approach and change the learning paradigm, aimed at a more dynamic and engaged process of knowledge construction in real life environment. Project teaching/learning is an approach that belongs to a new paradigm and involves students' research orientation in teaching and learning, during which already acquired knowledge is used, new ones are acquired and creativity, self-regulation and teamwork in students are developed. Such an approach should, in theory, enable the achievement of the outcomes and subject standards, as well as the development of subject and interdisciplinary competencies. In that sense, the aim of the paper is to, through the analysis of existing examples of several realized teaching projects, investigate and point out the potentials of project teaching for the development of interdisciplinary competencies and to offer an instrument for planning project teaching. After analyzing the flow of learning within the project approach, as well as examples of project teaching from our schools, it can be concluded that this model significantly contributes to the development of interdisciplinary competencies, defined by the Law on Fundamentals of Education (2017)